'X' marks the spot! Sedimentological, geochemical and palaeontological investigations of Upper Cretaceous (Maastrichtian) vertebrate fossil localities from the Vălioara valley (Densuş-Ciula Formation, Hațeg Basin, Romania). (July 2021) - Botfalvai, Gábor; Csiki-Sava, Zoltán; Kocsis, László; Albert, Gáspár; Magyar, János; Bodor, Emese R.; Ţabără, Daniel; Ulyanov, Alexey; Makádi, László
Abstract: At the beginning of the 20th century, the Croatian-Hungarian palaeontologist Ottokár Kadić discovered a rich Late Cretaceous vertebrate assemblage around Vălioara in the Haţeg Basin, including fossils of several dinosaurs and the lectotype of the eusuchian Allodaposuchus . These fossils were collected from seven main localities and have been housed in the collections of the Mining and Geological Survey of Hungary. However, the collection was mixed after World War II, and this unprovenanced material currently cannot be used for palaeoecological investigations. Nevertheless, the map marking the location of Kadić's sites has been recently uncovered, showing the positions of the fossiliferous localities, which allows matching these with the historically collected specimens using geochemistry. Based on Kadić's map, we georeferenced, relocated, and re-excavated these vertebrate-bearing outcrops, and documented their sedimentological context. Detailed stratigraphical investigations of the exposed successions indicate that this Vălioara material represents one of the oldest (earliest Maastrichtian) Late Cretaceous faunal assemblages known from the Haţeg Basin. The vertebrate remains collected during our new excavations around Vălioara represent turtles ( Kallokibotion ), crocodyliforms ( Allodaposuchus, Doratodon, ' Theriosuchus ', Acynodon ), dinosaurs ( Zalmoxes, Telmatosaurus, titanosaurs, theropods), and mammals. In order to determine potential geochemical differences among the sites, we selected several specimens with recorded stratigraphic position, measured their trace element compositions, and used these as independent proxies to assess the probable stratigraphic origin of the historical vertebrate fossils. Our detailed sedimentological, geochemical and palaeontological investigations around Vălioara contribute to a deeper understanding of the distribution, evolution and palaeoecology of the Haţeg vertebrate faunas during the latest Cretaceous. Highlights: GIS and REE geochemistry analyses reveal origin of unprovenanced museum fossils. Type localities of titanosaur Magyarosaurus, eusuchian Allodaposuchus are relocated. New well-preserved and diverse Maastrichtian vertebrate remains were collected. These fossils represent one the oldest faunal assemblages from the Haţeg Basin. The palaeoenvironment of this fauna is an otherwise rare, wetland-type floodplain.